Improving Post-Discharge Medication Adherence in Patients with CVD: A Pilot Randomized Trial - Oliveira-Filho,Alfredo D. (2014)
Background:Effective interventions to improve medication adherence are usually complex and expensive.Objective:To assess the impact of a low-cost intervention designed to improve medication adherence and clinical outcomes in post-discharge patients with CVD.Method:A pilot RCT was conducted at a teaching hospital. Intervention was based on the four-item Morisky Medication Adherence Scale (MMAS-4). The primary outcome measure was medication adherence assessed using the eight-item MMAS at baseline, at 1 month post hospital discharge and re-assessed 1 year after hospital discharge. Other outcomes included readmission and mortality rates.Results:61 patients were randomized to intervention (n = 30) and control (n = 31) groups. The mean age of the patients was 61 years (SD 12.73), 52.5% were males, and 57.4% were married or living with a partner. Mean number of prescribed medications per patient was 4.5 (SD 3.3). Medication adherence was correlated to intervention (p = 0.04) and after 1 month, 48.4% of patients in the control group and 83.3% in the intervention group were considered adherent. However, this difference decreased after 1 year, when adherence was 34.8% and 60.9%, respectively. Readmission and mortality rates were related to low adherence in both groups.Conclusion:The intervention based on a validated patient self-report instrument for assessing adherence is a potentially effective method to improve adherent behavior and can be successfully used as a tool to guide adherence counseling in the clinical visit. However, a larger study is required to assess the real impact of intervention on these outcomes.